PENGARUH PERTUMBUHAN PERUSAHAAN DAN STRUKTUR KEPEMILIKAN TERHADAP STRUKTUR MODAL DAN NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTI DI BEI - Kadek Anom Cakra Wibawa (Forum Manajemen STIMI Handayani Denpasar, 2013)
The objective of this research is to determine the significance of the effectof growth companies on capital structure and firm value, the effect of ownershipstructure on capital structure and firm value and the effect of capital structure onfirm value.This study population is a property company in Indonesia Stock Exchange in theperiod 2007 to 2009. The data used in this study is secondary data that the annualfinancial statements of 36 property companies on the Stock Exchange. Determinationof the sample in this study is based on random sampling technique of purposivesampling criteria are property companies with complete financial data in accordancewith the studied variables.The Model of this study using path analysis, the application of the tools of SPSSversion 13.0. The results of this study are at a significance level of 5% are found tosignificantly influence the growth of the company on capital structure. The growthof the company to the value of the company there is no significant effect. Further tothe ownership structure on capital structure there is no significant effect then thesame result is obtained, which is the ownership structure has no significant effecton firm value. The effect of capital structure on firm value where there is a negativesignificant effect.For the corporate, the best point of capital structure in many level, for the fund,can rise down the firm value. Furthermore it is recommended for further research toexamine other variables that effect the capital structure and the company’s growthbeyond the company’s ownership structure in addition to the property.